Scada as a Smarthome for Light Control Home Fence Door Control and Curtain Control Based on Schneider PLC M221 - Sanjaya, Kevin; Setiyani, Theresia Prima Ari (Institut Teknologi Dirgantara Adisutjipto, 2019)
Smarthome is made to help relieve human work in the field of automation in residential environments. The purpose of this system is to control the lamps, curtains, and fence doors, which are equipped with the HMI (Human Machine Interface) to display the process in real time. The system of this smarthome is made using Schneider TM221CE24R PLC as a controller. This smarthome controls the lamp with five different lighting brightness conditions by using a UV (Ultraviolet) sensor, controlling the open and close fence doors using the PIR (Passive Infrared) sensor, and controlling the curtains with three different conditions (open full, half closed, full lid) with the LDR sensor. The control of these Smarthome objects is displayed in an HMI (Human Machine Interface). The Operator can monitor the objects that are currently working through the HMI view. Through the testing stage of the tool, there is a conclusion that this smarthome can control objects well.